Diagnosis of Pulmonary Cryptococcosis in Respiratory Specimens from Immuno Compromised Iraqi Patients - Jabbar Salman Hassan (Journal of Global Pharma Technology, 2018)
Background: Cryptococcus neoformans, the causative agent of cryptococcosis, is a common encapsulated fungus that can cause a scope of sicknesses. Inhalation of organisms is the standard course of the disease that may stay spread to the lungs or experience hematogenous disseminations and reach to any organ through the body. Objective: The goal of this study was to determine the pulmonary Cryptococcosis in a specimen of immune compromised patients by utilizing traditional and molecular strategies. Methods: This study included a total of two hundred (n=200) clinical samples from 100 immuno compromised patients and control group included 100 samples from immune competent individuals were enrolled in this study during the period from the January2015 to February 2016. Result: Among those 100 immune compromised patients 43 (43%) were males and 57 (57%) were females , their mean ages was 54.56 ±16.46 years which ranged from 16 to 90 years, compared with 100 samples from apparently healthy individuals used as a control group. Out of 20 patients were PCR positive for pulmonary Cryptococcus’s 12(60%) were females and 8 (40%) were males. Five (5%) samples out of 100 immuno compromised patients were nigrosine stain positive; Three out of 100 samples were culture positive for C. neoformans. Conclusion: diagnosis and treatment of pulmonary cryptococcosis are as yet difficult. In any case, with early diagnosis and appropriate management, most non-AIDS patients with pulmonary cryptococcosis have a good prognosisKeywords: Pulmonary cryptococcosis, Cryptococcus neoformans, Bronichoalveolar lavage (BAL), Pleural effusion (PE), Nigrosin stain.